2017
DOI: 10.1093/nar/gkx394
|View full text |Cite
|
Sign up to set email alerts
|

Interstrand cross-links arising from strand breaks at true abasic sites in duplex DNA

Abstract: Interstrand cross-links are exceptionally bioactive DNA lesions. Endogenous generation of interstrand cross-links in genomic DNA may contribute to aging, neurodegeneration, and cancer. Abasic (Ap) sites are common lesions in genomic DNA that readily undergo spontaneous and amine-catalyzed strand cleavage reactions that generate a 2,3-didehydro-2,3-dideoxyribose sugar remnant (3’ddR5p) at the 3’-terminus of the strand break. Interestingly, this strand scission process leaves an electrophilic α,β-unsaturated ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 90 publications
2
52
0
Order By: Relevance
“…We exclude the possibility that EXO-3 acts to remove the 3′- α, β unsaturated aldehyde generated by NTH-1, as the exo-3(tm4374); apn-1(RNAi) knockdown mutant is no more sensitive to 5-hmU than the apn-1(tm6691) single mutant. Consistent with this notion, we have previously shown that EXO-3, unlike APN-1, lacks a 3′- to 5′-exonuclease activity, which might be the activity needed to remove such bulky and toxic 3′-blocked end 18 21 . In fact, it has been reported that diminishing UNG-1 activity to prevent production of AP sites recues the lifespan defect of the exo-3 mutants 23 .…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…We exclude the possibility that EXO-3 acts to remove the 3′- α, β unsaturated aldehyde generated by NTH-1, as the exo-3(tm4374); apn-1(RNAi) knockdown mutant is no more sensitive to 5-hmU than the apn-1(tm6691) single mutant. Consistent with this notion, we have previously shown that EXO-3, unlike APN-1, lacks a 3′- to 5′-exonuclease activity, which might be the activity needed to remove such bulky and toxic 3′-blocked end 18 21 . In fact, it has been reported that diminishing UNG-1 activity to prevent production of AP sites recues the lifespan defect of the exo-3 mutants 23 .…”
Section: Resultssupporting
confidence: 60%
“…This 3′-blocking lesion must be removed by one of the two conserved AP endonucleases/3′-diesterases, APN-1 and EXO-3, to produce a 3′-hydroxyl group for DNA repair synthesis 18 20 . If the 3′-blocking lesions are not efficiently removed, they can also generate DNA and protein crosslinks that become more deleterious than simple abasic sites 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Although the reaction of β‐elimination products of AP‐site cleavage with external alkoxyamines is known and has been exploited for their quantitative detection, the formation of covalent adducts with 2,7‐BisNP‐NH represents, to the best of our knowledge, the first example of the generation of stable adducts through the reaction of cleaved AP sites with polyamine ligands. In this context, it is interesting to mention the formation of stable interstrand cross‐links through the reaction of both uncleaved and cleaved AP sites with purine residues observed under native (nonreducing) conditions. Notably, in the latter case, the formation of the cross‐link was proposed to occur through a 1,4‐conjugate addition of N1 of a proximate adenine residue to the unsaturated aldehyde product of β‐elimination cleavage, which is reminiscent of the mechanism proposed above.…”
Section: Resultsmentioning
confidence: 99%
“…In analogy to other intrastrand and smallmolecule cross-links of AP sites, we expect this adduct to be genotoxic, representing ah urdle for DNA polymerases. [50,52,56] It may also be potentially harnessed for covalent targeting of AP sites and incorporation of reporter moieties, such as fluorophores or affinity tags for DNA pull-downstudies.…”
Section: Discussionmentioning
confidence: 99%
“…Interstrand cross-links (ICLs) are severe DNA lesions induced by numerous agents, including mitomycin C (MMC), cisplatin and endogenous products of lipid peroxidation [23,24]. By covalently linking both DNA strands, ICLs are highly toxic, as they can physically block DNA melting, transcription, and replication [25].…”
Section: Ivyspringmentioning
confidence: 99%